Effectiveness of Using Qur'an Hadith Module to Learning Outcomes - Dian Kusuma Wardani; Nur Janah; Hilyah Ashoumi (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the differences in learning outcomes of students who are taught without using modules and those taught by using modules. The sample in this study was taken by purposive sampling technique. Class VII C as the experimental class, as many as 33 students who were treated using Qur'an Hadith module and class VII D as the control class were 32 students who received treatment without using Qur'an Hadith module. The data collection methods used were tests and observations. Data processing and analysis techniques used is inferential statistics. Hypothesis testing uses the Mann-Whitney test. Mann Whitney U test was carried out, the results obtained were the Asymp value. Sig (2-tailed) of 0.000 <0.05, so it can be said that there is a significant effect on learning outcomes of the Quran Hadith using modules. Teaching materials using the Hadith Qur'an module according to the theory being studied basically can be applied in the learning process to improve the cognitive learning outcomes of students. The learning outcomes achieved by grade VII students at MTs Darussalam Ngesong can be maintained because they are already in the good category, but still need improvement or look for other factors that can improve student learning outcomes.